Legal Dynamics of Limited Liability Companies: Unveiling the Power of Commissioners and Shareholders to Take Legal Action Against Directors' Negligence - Sufiarina Sufiarina; Muhammad Ali; Mufrina Mufrina; Ahmad Maulana; Hendry Frand Tia (Universitas Negeri Semarang, 2023)
The Limited Liability Company (LLC) is characterized by its distinct juridical entity, effectively segregating its management group from shareholders. Operating as a business entity, the primary goal of an LLC is profit generation. Functioning as a corporate legal entity with legal personality, an LLC comprises three key organizational components: the General Shareholders’ Meeting, Directors, and Commissioners. Directors, or the Board of Directors (BOD), bear the responsibility of managing and representing the LLC both within and outside the legal realm. The position of BOD is mandated to be occupied by a natural person, or 'naturlijk person,' either as a single individual (Director) or collectively by two or more individuals (Board of Directors). Despite a stringent selection process for board positions, the inherent nature of directors as natural persons introduces the possibility of intentional or negligent errors in management, potentially leading to financial losses. In the face of such negligence, the pertinent question arises: can a commissioner (Board of Commissioners) and/or shareholders initiate legal action against a director or BOD, whose legal standing is as the company’s representative? To address this query, a comprehensive library research initiative is undertaken, focusing on the analysis of Article 97 and Article 98 of the Limited Liability Company’s legal statutes. This examination aims to elucidate the viable courses of action that can be pursued against the company in the event of directorial negligence. The research findings reveal that specific commissioners and/or shareholders, in the absence of a director's power of attorney, are granted the authority by the LLC’s legal statutes to initiate legal proceedings against the director or board of directors in a court of law.